Evaluasi Strategi Bisnis Perusahaan Start Up Menggunakan Bisnis Model Kanvas Pada PT XYZ - Akbar, Qomaruzzaman; Hilda Rossieta (Owner : Riset dan Jurnal Akuntansi, 2024)
With the development of technology, many start-up companies have been established. In November 2022 there were 2,400 startups in Indonesia. This study aims to evaluate the business strategy of start-up companies with the research object PT XYZ. PT XYZ engaged in the healthy food industry. This research is case study research with descriptive qualitative research methods. This research utilized Business Model Canvas as a basic theory and tool to evaluate business strategy. The results showed that PT XYZ implemented a broad differentiation strategy. The current focus of the company's strategy is to promote and introduce products to the public. The promotional strategy succeeded in increasing sales, but was unable to generate profits due to the large cost of promotion. There are several weaknesses in PT XYZ business model that can be improved to be able to generate profits. Adding customer segments in the form of B2B can potentially provide new revenues and bring benefit in promotions using other company resources. Additionally, the application of lean accounting that focused on cost reduction must be carried out for cost efficiency.